Assessment of geotechnical properties of bacteria treated soil - Chen, Huiwen. (2009)
Conventional soil improvement techniques such as mechanical compaction and chemical grouting are used to improve mechanical properties of soil and to reduce its hydraulic conductivity. However, such techniques have drawbacks such as high costs, environmental contamination and being energy intensive. Biological stabilization using bioclogging and biocementation is a new method to improve the mechanical properties of soil. This approach is more cost-effective and environmentally friendly. The primary objective of this research is to study the feasibility of applying biological approaches to sand to reduce its liquefaction susceptibility. Experiments were carried out to determine the optimal concentrations of nitrate and denitrifying bacteria to be used for this purpose.